Energy Storage: Design and Fabrication of New Nanostructured SnO2‐Carbon Composite Microspheres for Fast and Stable Lithium Storage Performance (Small 16/2014). Issue 16 (August 2014) - Ko, You Na; Park, Seung Bin; Kang, Yun Chan
<x xml:space="preserve">Abstract</x> A one‐pot method for metal oxide‐carbon composite microspheres with 3D ordered macroporous (3DOM) structures is introduced on page 3240 by Y. C. Kang and co‐workers. The 3DOM‐structured SnO2‐carbon microspheres are the first target material to show superior electrochemical properties as an anode material for lithium ion batteries. The newly developed process can be applied to the preparation of 3DOM‐structured metal oxide–carbon composite microspheres for wide applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>